CHD3 and CHD4 form distinct NuRD complexes with different yet overlapping functionality - Hoffmeister, Helen Andrea; Erdel, Fabian; Rippe, Karsten (Nucleic acids research, 2017)
Abstract: CHD3 and CHD4 (Chromodomain Helicase DNA binding protein), two highly similar representatives of the Mi-2 subfamily of SF2 helicases, are coexpressed in many cell lines and tissues and have been reported to act as the motor subunit of the NuRD complex (nucleosome remodeling and deacetylase activities). Besides CHD proteins, NuRD contains several repressors like HDAC1/2, MTA2/3 and MBD2/3, arguing for a role as a transcriptional repressor. However, the subunit composition varies among cell- and tissue types and physiological conditions. In particular, it is unclear if CHD3 and CHD4 coexist in the same NuRD complex or whether they form distinct NuRD complexes with specific functions. We mapped the CHD composition of NuRD complexes in mammalian cells and discovered that they are isoform-specific, containing either the monomeric CHD3 or CHD4 ATPase. Both types of complexes exhibit similar intranuclear mobility, interact with HP1 and rapidly accumulate at UV-induced DNA repair sites. But, CHD3 and CHD4 exhibit distinct nuclear localization patterns in unperturbed cells, revealing a subset of specific target genes. Furthermore, CHD3 and CHD4 differ in their nucleosome remodeling and positioning behaviour in vitro. The proteins form distinct CHD3- and CHD4-NuRD complexes that do not only repress, but can just as well activate gene transcription of overlapping and specific target genes.